Knowledge and attitude towards epilepsy among pharmacy students from Mumbai university - Limaye, Dnyanesh; Deshpande, Omkar; Gite, Pratik; Chavan, Sushil; Sydymanov, Arlan; Limaye, Vaidehi; Pitani, Ravi Shankar; Sathe, Sushama; Fortwengel, Gerhard (International Journal of Research in Medical Sciences, 2018)
Background: Epilepsy is a chronic disorder of the brain that affects people worldwide. The overall prevalence (3.0-11.9 / 1,000) and incidence (0.2-0.6/1,000) of epilepsy in India are comparable to the rates of high-income countries. The high prevalence of negative attitudes towards epilepsy has been highlighted by several studies. Pharmacy students represent a better-educated section of society regarding drugs and have the potential to create awareness, and influence attitudes towards the disease. Thus, it is important that they have the appropriate and updated knowledge and appropriate attitude towards epilepsy and antiepileptic drugs. Objective of the present study was to determine the Mumbai University pharmacy student’s awareness about epilepsy, so as to know the kind of education and awareness strategies that would be applicable to them. Methods: A cross-sectional study was carried out among students from Mumbai University, India during May-June 2017. Two hundred and fifty students were approached to participate in the study of which 213 agreed to participate (males: 107; females: 106). Pretested questionnaire was distributed and collected data was analyzed using IBM SPSS version 23. Results: Response rate for this study was 85.2% (213/250). Ninety six percent (204/213) of the participants had heard or read about epilepsy. Overall knowledge was poor (40.2%) and attitude was fair (75.3%). None of the participants were aware about recent research regarding hereditary nature of epilepsy. Only 2 (0.98%) students were aware how to perform the first aid in epilepsy. Only 6.8% participants felt that epileptics should participate in sports. Conclusions: The findings of this study show that, even with extensive curriculum covering diseases, drugs and relevant laws of land, the knowledge and attitude scores were low. There is a need to have focused education and campaigns to increase the knowledge and attitude towards epilepsy.